ANALISA SISTEM QR CODE UNTUK IDENTIFIKASI BUKU PERPUSTAKAAN - Prathivi, Rastri (Jurnal Pengembangan Rekayasa dan Teknologi, 2018)
Information books in the library will provide a special identity on any book title. Identity of the books stored in the library will allow the borrower book knows the book title, author, ISBN number, number of shelves where the books are stored and the number of books available in the library. Identity can be summarized in a QR Code.With the QR Code on the books, the user can obtain information about a book without having to connect to the database, simply scanning the QR Code Reader. To create a QR Code requires an application generator. In this study, the authors will develop case studies QR Code Generator library FTIK University of Semarang. QR Code Generator will convert alphanumeric data from a book into a two-dimensional image. Which will be attached to each book in the library.
Keywords: QR Code; identity books